The Influence Of Personal Branding and Value Cration On Business Performance Of UMKM Noodles in Bekasi City - Muthi Kamila; Novita Indriyani; Syahyono Syahyono; Muhammad Akmal Rasyid; Mukhammad Nadzim (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to study how personal branding and value creation impact the business performance of noodle SMEs in Bekasi City. This study uses a quantitative method by collecting data from a number of MSME actors in the area through questionnaires. According to the research, personal branding and value creation have a significant impact on the company's performance level. Strong personal branding can enhance the company's reputation, while value creation serves to provide additional relevant value to customers. The results of this research emphasize that effective personal branding and value creation strategies are crucial for supporting the sustainability and development of SMEs. The conclusions of this research can be used by entrepreneurs to create better marketing strategies.